Handbook of research on computational simulation and modeling in engineering - Miranda, Francisco; Abreu, Carlos (Advances in systems analysis, software engineering, and high performance computing (ASASEHPC), 2016)
This book is an authoritative reference source on the computer models and technologies necessary to enhance engineering structures and planning for real-world applications.